Plasmacytoid and conventional dendritic cells are early producers of IL-12 in Neospora caninum-infected mice - Teixeira, Luzia (2010)
Neospora caninum is a coccidian parasite causative of clinical infections in a wide range of animal hosts. The maturation and activation of splenic conventional dendritic cells (cDCs) and plasmacytoid dendritic cells (pDCs) were studied here in BALB/c mice challenged intraperitoneal with N. caninum tachyzoites. The number of cDCs was found to decrease in the spleen of the infected mice 12 h and 2 days after the parasitic challenge, whereas at day 5 after infection it was significantly above that of mock-infected controls. In contrast, the number of splenic pDCs did not change significantly on infection. In the infected mice, both cell subtypes displayed an activated phenotype with upregulation of costimulatory and MHC class II molecules. This stimulatory effect was more marked at the earliest assessed time point after infection, 12 h, when a clear increase in the frequency of cDCs (CD8alpha(+) and CD8alpha(-)) and pDCs producing interleukin-12 (IL-12) was also observed. N. caninum tachyzoites could be observed by confocal microscopy associated with sorted DCs. Overall, these results present the first evidence that both cDCs and pDCs mediate in vivo the innate immune response to N. caninum infection through the production of IL-12, a key cytokine for host resistance to neosporosis.